2005
DOI: 10.1093/geront/45.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Micromanaging Death: Process Preferences, Values, and Goals in End-of-Life Medical Decision Making

Abstract: Very few individuals may desire the standard approach to advance care planning whereby preferences for specific life-sustaining treatments are documented and these requests are strictly followed near death. Instead, patient autonomy may be better served by emphasizing discussion of process preferences and leeway in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 18 publications
7
133
1
2
Order By: Relevance
“…3,8,9 Physicians often underestimate the emotional resilience of patients and their desire to be involved in this decision-making process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8,9 Physicians often underestimate the emotional resilience of patients and their desire to be involved in this decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 This lack of planning can have negative consequences including emotional distress for patients and caregivers, and medical care that is inconsistent with patients' wishes. [8][9][10] Unfortunately, even when ACP discussions are initiated, they are often ineffective because of poor patient-physician communication and patients' lack of sufficient medical knowledge to engage in these discussions.…”
Section: Introductionmentioning
confidence: 99%
“…This research reveals that the majority of patients prefer that family members or physicians have input into the decisions. [34][35][36][37][38] In these studies, as in the ones examining the stability of patients' preferences, the patients who were most likely to want their wishes to prevail were the ones who more often wrote advanced directives. 38 …”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…3,4 Therefore it has been suggested that physicians should not only pay attention to the preferences of the patient in relation to specific medical situations that might arise, but also to how the patient wants medical decisions to be made if he should lose competence, e.g., does the patient wish other people to be involved, who does he wish to be involved and to what degree? 5,6 To examine the involvement of family and/or other people in medical decision-making from the perspective of the patient's preferences, we investigated advanced lung cancer patients during the course of their disease. The research questions were:…”
Section: Introductionmentioning
confidence: 99%